Educating for ethical survival - Breakey, Hugh; Harris, Howard; Highfield, Charmayne; Schwartz, Michael (Emerald Publishing Limited, 2020)
Research in Ethical Issues in Organizations (REIO) is a double-blind, peer-reviewed series that publishes rigorous academic research into organizational ethics from a wide variety of disciplinary perspectives. In this volume, Educating for Ethical Survival, a special section focuses on the challenges of teaching ethics to practically minded students, aiming to make the task of teaching applied ethics more tractable and constructive. Further contributions explore a range of aspects of ethical survival. Topics covered include: propensity to moral disengagement ability to survive ethically amid discord finding ethical survival globally ethical survival of students content of social ethics courses why reflection is important in personal learning as a global citizen. Suited for professionals, educators and researchers, this book poses questions about the nature of ethical survival in a rapidly changing world and about the role of ethics in organizations.